Mortalidade de crianças nascidas de muito baixo peso em uma maternidade pública de Belo Horizonte: um estudo a partir de sistemas de informação - Ana Maria de Jesus Cardoso (1999)
The infant mortality rate is traditionally used as an indicator of the general health of a community, and can be used as a sentinel event of the quality of care provided. With the objective of evaluating the infant mortality of very low birth weight children born in a public maternity hospital of level II complexity, with discrimination between the period of hospitalization in the maternity hospital itself and the period after hospital discharge, a prospective historical study was carried out. it consisted of the analysis of records of existing information systems: Perinatal Computer System [Sistema Informático Perinatal], adopted in the maternity, Live Births Information System [Sistema de Informação de Nascidos Vivos] and Mortality Information System [Sistema de Informação de Mortalidade]. The 17,791 records of children born alive at the Odete Valadares Maternity [Maternidade Odete Valadares], in the period between 01/01/1992 to 12/31/1996, with birth weight ≥ 500 g, highlighting 817 children with birth weight of up to 1500 g were evaluated. During the period of this study, the Odete Valadares Maternity [Maternidade Odete Valadares] accounted for 5.5% of hospital deliveries of live births to women residing in Belo Horizonte, with this percentage being modified to 12.2% when this group was limited to low birth weight newborns, and for 17.8%, when it came to those with very low birth weight, characterizing the importance of this institution, at the municipal level, for assisting childbirth and high-risk newborns, despite not having an intensive care unit. A global mortality rate of live births weighing ≥ 500 g of 28 per thousand was also observed, with a reduction from the value of 30 per thousand obtained in 1992 to 21 per thousand in 1996. As for newborns with very low weight, the global mortality coefficient was 435 per thousand, with a tendency to stability in the 5 years evaluated, with the lowest rate observed in 1994 (385 per thousand). As for the latter group, the following factors related to hospital mortality were found using the multivariate logistic regression model: estimated gestational age (odds ratio (OR)=0.4468 and p=0.000), birth weight (OR=0.7024 and p=0.0169) and Apgar score at 5 minutes of life (OR=0.4198 and p=0.0004). The result suggests, as protective factors for hospital mortality, the estimated gestational age, the highest birth weight, and the Apgar score at 5 minutes of life ≥ 7. Among the 519 very low birth weight children born to women living in Belo Horizonte, 247 were discharged from home, and 13 of them (5.3%) died during the first year of life through the Mortality Information System [Sistema de Informação de Mortalidade], and 42 were transferred to another service, with 15 dying. (35.7%). Infectious causes were the most frequently reported as the underlying cause of these deaths. Thus, through the use of available information systems, it was possible to evaluate some aspects related to the mortality of very low birth weight children born in an institution, both in the hospital environment and after discharge to their homes, from a perspective of the insertion of that same institution in the information and health care system.